Gut microbiota metabolizes nabumetone in vitro: Consequences for its bioavailability in vivo in the rodents with altered gut microbiome. (2nd November 2019) - Jourova, Lenka; Anzenbacher, Pavel; Matuskova, Zuzana; Vecera, Rostislav; Strojil, Jan; Kolar, Milan; Nobilis, Milan; Hermanova, Petra; Hudcovic, Tomas; Kozakova, Hana; Kverka, Miloslav; Anzenbacherova, Eva
Abstract: 1. The underlying microbial metabolic activity toward xenobiotics is among the least explored factors contributing to the inter-individual variability in drug response. 2. Here, we analyzed the effect of microbiota on a non-steroidal anti-inflammatory drug nabumetone. 3. First, we cultivated the drug with the selected gut commensal and probiotic bacteria under both aerobic and anaerobic conditions and analyzed its metabolites by high-performance liquid chromatography (HPLC) with UV detection. To analyze the effect of microbiota on nabumetone pharmacokinetics in vivo, we administered a single oral dose of nabumetone to rodents with intentionally altered gut microbiome - either rats treated for three days with the antibiotic imipenem or to germ-free mice. Plasma levels of its main active metabolite 6 methoxy-2-naphthylacetic acid (6-MNA) were analyzed at pre-specified time intervals using HPLC with UV/fluorescence detection. 4. We found that nabumetone is metabolized by bacteria to its non-active metabolites and that this effect is stronger under anaerobic conditions. Although in vivo, none of the pharmacokinetic parameters of 6-MNA was significantly altered, there was a clear trend towards an increase of the AUC, Cmax and t 1/2 in rats with reduced microbiota and germ-free mice.